Analysis of risk factors of involvement of seminal vesicles in patients with prostate cancer undergoing radical prostatectomy - Dall'Oglio,Marcos F. (2004)
OBJECTIVE: To determine through preoperative serum PSA level, Gleason score on biopsy and percentage of fragments affected by tumor on biopsy, the probability of involvement of the seminal vesicles. MATERIALS AND METHODS: During the period between March 1991 to December 2002, we selected 899 patients undergoing radical prostatectomy for treatment of localized prostate adenocarcinoma. The analyzed preoperative variables were PSA, percentage of positive fragments and Gleason score on the biopsy. Pre-operative PSA was divided in scales from 0 to 4.0 ng/mL, 4.1 to 10 ng/mL, 10.1 to 20 ng/mL and > 20 ng/mL, Gleason score was categorized in scales from 2 to 6. 7 and 8 to 10, and the percentage of affected fragments was divided in 0 to 25%, 25.1% to 50%, 50.1% to 75%, and 75.1% to 100%. All these variables were correlated with the involvement of seminal vesicles in the surgical specimen. RESULTS: Of the 899 patients under study, approximately 11% (95% CI, [9% - 13%]) had involvement of seminal vesicles. On the multivariate analysis, when PSA was < 4, the Gleason score was 2 to 6, and less than 25% of fragments were involved on the biopsy, only 3.6%, 7.6% and 6.2% of patients respectively, had involvement of seminal vesicles. On the multivariate analysis, we observed that PSA, Gleason score and the percentage of involved fragments were independent prognostic factors for invasion of seminal vesicles. CONCLUSION: The preoperative variables used in the present study allow the identification of men with minimal risk (lower than 5%) if involvement of seminal vesicles.